Review of iOS malicious application analysis - Yixiang ZHU; Kang ZHANG; Weiqing WANG (Dianxin kexue)
The security architecture and distribution of iOS were introduced.The threats to user's data security and privacy from iOS malicious applications were analyzed.The reasons that the number of iOS malicious applications is less than Android malicious applications were discussed.The attacking methods of emerging iOS malicious applications were summed up.And prospect for future mitigation and confrontation strategies were given.